Izboljšanje termodinamičnih lastnosti hladilnih stolpov na naravni vlek - Širok, Brane (Strojniški vestnik, 2007)
The velocity and temperature fields above droplet eliminators inside a natural-draft cooling tower of the Doel-3 powerplant (Belgium) were determined using the CTP (Cooling Tower Profiler) method. The measurements show regions of high velocities and low temperatures of air at the cooling tower circumference, leading to locally impaired heat and mass transfer. The established phenomenological relations enable the solution of this problem, which can be achieved by a variation of the fill height and the water mass-flow rate. The influence of these two parameters was analysed numerically. A 3D numerical simulation of a single-phase turbulent airflow wasperformed. Local values of the air velocity and air temperature were included in the numerical model through source terms. The numerical results present the analysis of local irregularities and their influence on the overall cooling-tower characteristics. Experimental and numerical results for the velocity and temperature fields in a cooling towerćs transverse section are presented, followed by a procedure for reducing irregularities in the cooling towerćs operation. This procedure includes the increase of the fill height and the rearrangement of the local cooling-water mass-flow rate in the cooling towerćs transverse section. In the numerical model these two parameters were modelled by a local modification of the source terms. Modifiedsource terms of the model lead to more uniform aero-thermodynamic properties in the tower and consequently to a higher cooling-tower efficiency. The paper presents a complete diagnostic method of local anomalies, based on the case of a representative Doel-3 cooling tower. The method is based on experimental and numerical modelling of the transport phenomena inside the cooling tower. It makes it possible to increase the efficiency of the cooling towerćs operation. The calculated mean heat-flux density was increased by 2.8% in this particular case.
Keywords: hladilni stolpi; prenos toplote; prenos snovi; termodinamične lastnosti; numerična analiza